Evaluation of hepatoprotective potential of tinospora Cordifolia extracts in fructose-induced Experimental diabetic rats (Funded Work) - DUBEY PREETY; SRIVASTAVA NALINI (International Journal of Pharma and Bio Sciences, 2017)
Diabetes has become an international health problem as it is one of the most common non communicable metabolic disorders affecting various organs. Present study is aimed to evaluate the hepatoprotective potential of Tinospora cordifolia (Tc) in experimental diabetes in rats. Type 2 diabetes mellitus (T2DM) was induced by feeding of fructose solution for three weeks and a single intraperitoneal injection of streptozotocin, to the rats. Blood glucose level was monitored every week, the rats showing glucose level ≥ 250 mg/dl on day 22nd were selected for the study. Aqueous, ethanolic and methanolic extracts of Tc were given to the diabetic and control rats. The results showed that all the extracts and Liv-52 treatment tend to normalize the altered parameters of liver function test in the serum and the liver of diabetic rats. Further studies are required to identify the active component of Tc and unravel the mechanism of its action.